Penerapan Hukum terhadap Dugaan Fasilitasi Transaksi Judi Online oleh PT Espay Debit Indonesia Koe (DANA) - Martina Martina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the application of the law to the alleged facilitation of online gambling transactions by PT Espay Debit Indonesia Koe (DANA), which allegedly distributed funds of IDR 5.37 trillion in illegal activities. This case is in the spotlight because it shows the weakness of the digital financial supervision system in Indonesia and raises questions about the limits and forms of legal accountability of fintech operators in preventing misuse of services. The research method used is normative juridical with a descriptive qualitative approach, using primary, secondary, and tertiary legal materials to analyze applicable regulations and supervisory practices. The results of the study show that although DANA does not directly commit a criminal act of gambling, negligence in implementing transaction supervision mechanisms, including monitoring suspicious transaction patterns, can give rise to certain forms of legal liability. These findings underscore the importance of prudence and compliance with anti-money laundering regulations in fintech operations. This study recommends strengthening fintech regulations, implementing stricter Know Your Customer (KYC), increasing synergy between OJK, PPATK, and the Police, and establishing a more integrated and responsive digital transaction supervision system to prevent similar crimes in the future.